The Relationship Between Migraine or Severe Headache and Chronic Health Conditions: A Cross-Sectional Study from the National Health Interview Survey 2013–2015 - Minen, Mia T (Pain Med, 2019)
OBJECTIVE: To estimate the prevalence of having at least one or two or more chronic health conditions among US adults with self-reported migraine or severe headaches. DESIGN: Cross-sectional study. METHODS: Using data collected from the 2013–2015 National Health Interview Survey, we examined adults with and without migraine or severe headache and associations with chronic obstructive pulmonary disease, cancer, heart disease, stroke, diabetes, and hypertension. We calculated point estimates, variances, and 95% confidence intervals and conducted bivariate and multivariable logistic regression modeling to examine the relationships between migraine or severe headache and each of the chronic health conditions, as well as multinomial modeling, to examine the relationship between migraine or severe headache and having one or more chronic health conditions. RESULTS: A total of 104,926 people were in the study. Adults aged 18 to 44 years (18.2%), women (20.1%), and those with some college education (17.6%) had the greatest proportion with migraine or severe headache (P < 0.0001). Using multinomial modeling with the number of chronic health conditions as the dependent variable, adults reporting migraine had an increased odds of reporting a single chronic health condition (adjusted odds ratio [aOR] = 1.7, 95% confidence interval [CI] = 1.6–1.8) and more than double the odds of reporting two or more chronic health conditions (aOR = 2.5, 95% CI = 2.3–2.8) compared with adults who did not have migraine or severe headache. CONCLUSIONS: Our study confirms observed relationships between migraine or severe headache and chronic health conditions and supports the need for further research to uncover the shared biological pathways.